A study report on the effect of COVID-19 pandemic in providing in-and-out-patient psychiatric services in a level-3 COVID hospital - Deepa Singh; Richa Pandey; Gaurav S. Yadav; Prabhat K. Agrawal; Amil H. Khan; Tapas K. Aich (Indian Journal of Psychiatry)
Background: COVID-19 pandemic disrupted all routine and emergency hospital services, including our out-and-in-patient psychiatric services. Aim: To study the effect of the COVID-19 pandemic and subsequent lockdown in providing in-and-out-patient psychiatric services and the experience of tele-consultation services in our level-3 COVID hospital. Materials and Methods: We conducted a retrospective observational study using an administrative database at psychiatry in-and-out-patient department. All the cases that were reported to us, through emergency Out-Patient Department (OPD) and tele-consultation OPD, from April 2020 to October 2020, were included in the study. Data, thus obtained, were compared with the out-and-in-patient data during the same period on the previous year. Results: During the study period, there was a decline in out-patient registration of patients by 94.5%, and a reduction in admission rate was 75.5%, in comparison with the previous year. During 3 months of tele-consultation service provided, 23.5% of patients had the diagnosis of depression, 21.4% of them had various types of headaches, 15.9% of patients had psychosis, 15.3% had anxiety disorders, and 8.8% had a bipolar-affective disorder. Conclusion: Being a level-3 COVID hospital, our hospital suffered significantly in relation to psychiatric in-and-out-patients attendance and service recipients during the study period of COVID-19 pandemic.